Dietary supplementation with 1‐kestose induces altered locomotor activity and increased striatal dopamine levels with a change in gut microbiota in male mice - Altanzul Altaisaikhan; Kazufumi Yoshihara; Tomokazu Hata; Noriyuki Miyata; Yasunari Asano; Takafumi Suematsu; Yoshihiro Kadota; Nobuyuki Sudo (Physiological Reports, 2023)
Abstract 1‐Kestose (KES), a dietary fiber and prebiotic carbohydrate, benefits various physiological functions. This study aimed to examine whether diets supplemented with KES over three consecutive generations could significantly affect some host physiological aspects, including behavioral phenotypes and gut microbial ecology. Mice that received KES‐supplemented diets for three generations demonstrated increased activity compared with those fed diets lacking KES. Furthermore, the KES group showed increased striatal dopamine (DA) and serotonin (5‐HT) levels. The observed increase in DA levels within the striatum was positively correlated with locomotor activity in the KES group but not in the control (CON) group. The α‐diversities were significantly lower in the KES group compared to the CON group. The three‐dimensional principal coordinate analysis revealed a substantial distinction between the KES and CON groups across each generation. At the genus level, most gut microbiota genera exhibited lower abundances in the KES group than in the CON group, except for Bifidobacteria and Akkermansia. Spearman's rank‐order analysis indicated significant negative correlations between the striatal DA levels and α‐diversity values. These findings suggest that prolonged supplementation with KES may stimulate increased locomotor activity along with elevated striatal DA levels, which are potentially associated with KES‐induced alterations in the gut microbiota.